Autocrine C‐peptide mechanism underlying INS1 beta cell adaptation to oxidative stress. Issue 7 (October 2014) - Luppi, Patrizia; Drain, Peter
Abstract Background Excessive generation of reactive oxygen species (ROS) causing oxidative stress plays a major role in the pathogenesis of diabetes by inducing beta cell secretory dysfunction and apoptosis. Recent evidence has shown that C‐peptide, produced by beta cells and co‐secreted with insulin in the circulation of healthy individuals, decreases ROS and prevents apoptosis in dysfunctional vascular endothelial cells. In this study, we tested the hypothesis that an autocrine activity of C‐peptide similarly decreases ROS when INS1 beta cells are exposed to stressful conditions of diabetes. Methods Reactive oxygen species and apoptosis were induced in INS1 beta cells pretreated with C‐peptide by either 22 mM glucose or 100 μM hydrogen peroxide (H2O2). To test C‐peptide's autocrine activity, endogenous C‐peptide secretion was inhibited by the KATP channel opener diazoxide and H2O2‐induced ROS assayed after addition of either exogenous C‐peptide or the secretagogue glibenclamide. In similar experiments, extracellular potassium, which depolarizes the membrane otherwise hyperpolarized by diazoxide, was used to induce endogenous C‐peptide secretion. ROS was measured using the cell‐permeant dye chloromethyl‐2′, 7′‐dichlorodihydrofluorescein diacetate (CM‐H2‐DCFDA). Insulin secretion and apoptosis were assayed by enzyme‐linked immunosorbent assay. Results C‐peptide significantly decreased high glucose‐induced and H2O2‐induced ROS and prevented apoptosis of INS1 beta cells. Diazoxide significantly increased H2O2‐induced ROS, which was reversed by exogenous C‐peptide or glibenclamide or potassium chloride. Conclusions These findings demonstrate an autocrine C‐peptide mechanism in which C‐peptide is bioactive on INS1 beta cells exposed to stressful conditions and might function as a natural antioxidant to limit beta cell dysfunction and loss contributing to diabetes. Copyright © 2014 John Wiley & Sons, Ltd.